Towards the Application of Open Source Software in Developing National Electronic Health Record- Narrative Review Article. - AMINPOUR, Farzaneh; SADOUGHI, Farahnaz; AHMADI, Maryam (Iranian Journal of Public Health, 2013)
Electronic Health Record (EHR) is a repository of patient health information shared among multiple authorized users. As a modern method of storing and processing health information, it is a solution for improving quality, safety and efficiency of patient care and health system. However, establishment of EHR requires a significant investment of time and money. While many of healthcare providers have very limited capital, application of open source software would be considered as a solution in developing national electronic health record especially in countries with low income. The evidence showed that financial limitation is one of the obstacles to implement electronic health records in developing countries. Therefore, establishment of an open source EHR system capable of modifications according to the national requirements seems to be inevitable in Iran. The present study identifies the impact of application of open source software in developing national electronic health record in Iran.